"Almost a role model of what we would like to do everywhere": British American Tobacco in Cambodia. (24th November 2004) - MacKenzie, R; Collin, J; Sopharo, C; Sopheap, Y
Abstract : Objectives: To examine British American Tobacco's (BAT's) renewed interest in Cambodia from the early 1990s, reviewing negotiations to establish a joint venture and the subsequent conduct of BAT Cambodia (BATC). Methods: Analysis of previously confidential BAT documents relevant to the Cambodian market. Results: With the advent of comparative political stability in the early 1990s, BAT was quick to explore the possibilities for investment. The Cambodian government urgently required foreign investment, offering inducements and assistance to investors. In developing a joint venture, BAT saw a cost effective opportunity to dominate the local market and to defend its regional interests, Cambodia being viewed as strategically located to support smuggling. Given minimal advertising regulation, BATC have undertaken wide ranging promotions and sought to prevent advances in tobacco control. Conclusions: BATC is presented as a contribution to Cambodia's regeneration, but the documents highlight its exploitation of state incapacity and an escalating threat to public health.